An Evaluation of Sterilization and Structural Integrity of Enamel of Diabetes Teeth - Dr. John Harry Bravado (International Journal of Medical Science And Diagnosis Research, 2018)
Diabetes mellitus (DM) and periodontitis are common chronic diseases in adults globally [1]. These diseases are thought to be associated biologically. A number of studies have proposed the mechanisms to explain their relationship including microvascular diseases, changes in components of gingival crevicular fluid, changes in collagen metabolism, an altered host response, altered subgingival flora, genetic predisposition and nonenzymatic glycation [2]. Keywords: Micro, Vascular, Diseases, Pathogenic organism